Core to toe temperature gradient during early post cardiac surgery period does not correlate with cardiac output in pediatric population - Muhammed Riyas K Rahmath; Jiju John; William Greer; Jai P Udassi; Akhlaque Nabi Bhat (Wolters Kluwer Medknow Publications, 2017)
Hypothesis: Core to toe temperature gradient measured during early post-operative phase will not correlate with oxygen extraction ratio, a surrogate marker for Cardiac Output. Materials and Method: This is a prospective observational study in pediatric cardiac intensive care unit, at Hamad General Hospital, Doha Qatar. Patients who underwent biventricular repair on cardio-pulmonary bypass were included. At hour 1, 4, 8 and 12 post surgery, core to toe temperature gradient was recorded. At similar time intervals, Oxygen extraction ratio (OER) was calculated using formula SaO2 - SvO2/ SaO2 x 100, where SaO2 is systemic arterial saturations and SvO2 is mixed venous (central) saturations. Results: There were total of 99 patients enrolled in the study. The median age was 10.93 months (range 1.93 -176.7 months). Male: Female ratio was 1.1:1. At each of 1,4, 8 and 12 hours, Pearson's pairwise correlation coefficient (r) was calculated between oxygen extraction ratio and core-toe temperature gradient. The associated confidence interval, coefficient of determination (r2) and p-value are: [1-hour: r =0.0565 (-0.1512 to 0.2595), r2=0.0032 p=0.5 [4-hour: r = 0.2094 (0.0024 to 0.3992), r2=0.0439, p=0.047], [8-hour: r = 0.2113 (0.0079 to 0.3979), r2=0.0446, p= 0.042], [12 hour: r =0.2776 (0.0672 to 0.4643), r2=0.0771, p = 0.010]. There was no correlation between the core to toe temperature gradient and oxygen extraction ratio at the first hour mark and a weak correlation was observed at the 4 hour, 8 hour and 12 hour mark. Conclusions: The core to toe temperature gradient does not correlate with the oxygen extraction ratio (surrogate marker of cardiac output) during the early post-operative phase in pediatric patients following cardiac surgery under cardiopulmonary bypass. There are multiple factors effecting this relationship and need further studies.